2014
DOI: 10.1093/aob/mcu098
|View full text |Cite
|
Sign up to set email alerts
|

Using virtual 3-D plant architecture to assess fungal pathogen splash dispersal in heterogeneous canopies: a case study with cultivar mixtures and a non-specialized disease causal agent

Abstract: The results show agreement with previous data obtained using experimental approaches. They demonstrate that in order to maximize the potential mixture efficiency against a splash-dispersed pathogen, optimal susceptible/resistant cultivar proportions (ranging from 1/9 to 5/5) have to be established based on host resistance levels. The results also show that taking into account dispersal processes in explicit 3-D plant canopies can be a key tool for investigating disease progression in heterogeneous canopies suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 51 publications
4
24
0
Order By: Relevance
“…Here we focused on individual dispersal events and not on the whole epidemic, in order to better understand mechanisms related to canopy architecture. Other studies have investigated the effect of cultivar mixtures on epidemics, and shown that mixture effects can be amplified by successive dispersal cycles (Gigot et al, 2014).…”
Section: Modelling Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we focused on individual dispersal events and not on the whole epidemic, in order to better understand mechanisms related to canopy architecture. Other studies have investigated the effect of cultivar mixtures on epidemics, and shown that mixture effects can be amplified by successive dispersal cycles (Gigot et al, 2014).…”
Section: Modelling Approachmentioning
confidence: 99%
“…Cultivar mixtures consist of growing different cultivars together in the same field. This cultural practice can provide a reduction of disease propagation if mixtures are adequately designed, in particular if chosen cultivars have contrasting levels of resistance to the targeted disease (Finckh and Wolfe, 2006;Gigot et al, 2014). Moreover, it makes it possible to grow cultivars having interesting qualities (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understandably, fungal pathogens are likely to benefit from increased moisture, which can promote fungal spore germination, mycelium growth, and initiation of infection (Woods et al ., ; Strengbom et al ., ). In addition, the dispersal of spores could be affected by precipitation over short distances both positively (dispersal through rain‐splash droplets) and negatively (removing spores from air and leaf surfaces before they have attached) (Gigot et al ., ). For host plants, altered precipitation can alter fungal infections.…”
Section: Introductionmentioning
confidence: 97%
“…The protective effect of varietal admixture was nevertheless lower when admixture grain was too fine. Indeed, while use of varietal admixture or multi-lines can decrease pathogen epidemics, especially with regard to soil-borne diseases or splash dispersed fungi (Mundt, 2002;Trutmann et al, 1996), a too fine grain in admixture can translate in inefficient plant protection when admixture is at the individual plant level, since susceptible plants may thus grow within pathogen average dispersal distance (Gigot et al, 2014;Skelsey and Newton, 2014;Garett and Mundt, 1999), and our results suggest that fine scale varietal admixture are indeed associated with increased reports of anthracnose (Farmers' experience of anthracnose is lower when admixture is practiced in blocks and rows compared to when varieties are planted haphazardly or alternated one after the other). Admixture and cultivation of other species were rather expected effects of acknowledged beneficial practices (Mulumba et al, 2012), and they definitely seem to fit in a set of potentially sustainable strategies against the disease, provided the admixture grain be greater than dispersal ability of Colletotrichum.…”
Section: Impact Of Disease Experience On Cropping Systemsmentioning
confidence: 99%